Fear the invisible man [videorecording (DVD)] - Wells, H. G. (Herbert George), 1866-1946; Hayman, David; Arnold, Mark; Calvey, Mhairi (Trinity Creative, 2023)
After taking in her medical school colleague, who has become invisible, a widow witnesses his gradual descent into madness. As he schemes to unleash a reign of terror and murder, she must find a way to stop him from wreaking havoc across the city.